Development of integrated multisensor isothermal amplification with nurcleic acid lateral flow system for point of care biosensor assay - Yean, Chan Yean (Pusat Pengajian Kesihatan, 2016)
1 developed prototype provides a method of definitive detection multiplex for loop-mediated isothermal amplification AMP). Method of amplicons detection relates to a label-based lateral flow dipstick device. The device comprises an orbent pad and a reaction pad. The reaction pad immobilized with more than two sorts of antibodies to detect tiple dual-labeled LAMP amplicons. A first line on the reaction pad, a chromatography control line, is an Tunological component that capable of binding to an enzyme-labeled antibody. The second and third lines, known as ■ lines, are also an immunological component that capable of specifically binding to labeled site of LAMP amplicons ch are another labeled site are bound to enzyme-labeled antibody to form the sandwich complexes. The enzymeeled antibody produces a visual red color by which it is pre-coated with gold nanoparticles. In specific, the present totype simplifies the multi-steps of mLAMP reagent preparation, reduces the risk of carry-over contamination, ease of A.MP amplicons detection and improved the credibility of the study. The ready-to-use thermostabilized mLAMP gents can be potentially applied as a diagnostic kit for diagnosis of diseases on field or in clinical settings.